Vaccines for cancer immunotherapy : a comprehensive evidence-based review on current status and future perspectives - Rezaei, Nima; Keshavarz-Fathi, Mahsa (Academic Press, an imprint of Elsevier, 2019)
Therapeutic cancer vaccines represent a type of active cancer immunotherapy. Clinicians, scientists, and researchers working on cancer treatment require evidence-based and up-to-date resources relating to therapeutic cancer vaccines. Vaccines for Cancer Immunotherapy provides a reference for cancer treatment for clinicians and presents a well-organized resource for determining high-potential research areas. The book considers that this promising modality can be made more feasible as a treatment for cancer. Chapters cover cancer immunology, general approaches to cancer immunotherapy, vaccines, tumor antigens, the strategy of allogeneic and autologous cancer vaccines, personalized vaccines, whole-tumor antigen vaccines, protein and peptide vaccines, dendritic cell vaccines, genetic vaccines, candidate cancers for vaccination, obstacles to developing therapeutic cancer vaccines, combination therapy, future perspectives and concluding remarks on therapeutic cancer vaccines.